2015
DOI: 10.1097/jto.0000000000000536
|View full text |Cite|
|
Sign up to set email alerts
|

Increasing Physical Activity and Exercise in Lung Cancer: Reviewing Safety, Benefits, and Application

Abstract: Lung cancer continues to be a difficult disease frequently diagnosed in late stages with a high mortality and symptom burden. In part because of frequent lung comorbidity, even lung cancer survivors often remain symptomatic and functionally limited. Though targeted therapy continues to increase treatment options for advanced-stage disease, symptom burden remains high with few therapeutic options. In the last several decades, exercise and physical activity have arisen as therapeutic options for obstructive lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 118 publications
(167 reference statements)
1
93
0
4
Order By: Relevance
“…and disability related to sedentary lifestyles (35). Other authors found that rehabilitation is feasible, safe and can even prevent deterioration of the general condition in lung cancer patients (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and disability related to sedentary lifestyles (35). Other authors found that rehabilitation is feasible, safe and can even prevent deterioration of the general condition in lung cancer patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…The median number of days between CPET and surgery was 44 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. There was no significant difference between the two groups ( Table 2).…”
Section: Parameters Of Prehabilitation and Surgerymentioning
confidence: 99%
“…Physical activity and exercise are beneficial in terms of the primary and secondary prevention of cancer as well as cancer-related and all-cause mortality [36]. Future research should investigate the degree to which prehabilitation exercise programmes as an adjunct to traditional cancer therapies present an advantage for patients in terms of survival and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity during cancer treatment has been shown to improve various quality of life measures (108, 109). These benefits are likely generalizable to hematologic malignancies including MPNs (110).…”
Section: Novel Nonpharmacologic Approachesmentioning
confidence: 99%